Flowering and fructification of arabica Coffee in different Coffee areas of Brazil - Camargo, Ângelo Paes de (Pesquisa Agropecuaria Brasileira, 2014)
Coffea arabica L. is a photoperiodic plant with floral bud differentiation when days are shorter than 13-14 hours. Short-day condition occurs throughout the year in the equatorial belt between 40 north and south latitude. Outside this belt, where all the Brazilian coffee areas are located, the days are short enough to promote floral bud defferentiation only after the autumn equinox, in March. The floral buds will develop and approach anthesis, about four months later in the spring, when the rainy season begins; However, in the coffee areas of the Brazilian Northeast the rainy season is delayed about six months, coming after the critical flowering and fructification phases. The introduction of a nonphotoperiodic variety, as the semperflorens, which is able to flower and fructify during the local rainy season, may bring considerable benefit to the regional coffee production.